Multisystem inflammatory syndrome in children during the COVID-19 waves: data from the Juvenile Inflammatory Rheumatism cohort - Robin Kechiche; Charlotte Borocco; Fanny Bajolle; Alexandre Belot; Sylvaine Poignant; Noémie Lachaume; Lucas Percheron; Ulrich Meinzer; Clara Mertes; Véronique Despert; Luc Morin; Virginie Lambert; et al. (Frontiers Media S.A., 2023)
IntroductionMultisystem inflammatory syndrome in children (MIS-C) is a new condition that first appeared in children and adolescents during the COVID-19 pandemic. We aimed to describe the diagnostic course, clinical and biological manifestations, and treatment of MIS-C during the first three COVID-19 waves.MethodsWe extracted patient data from the Juvenile Inflammatory Rheumatism (JIR) cohort. We analyzed data for patients meeting the World Health Organization diagnostic criteria for MIS-C from the start of the COVID-19 pandemic from March 2020 to June 30, 2021. We then compared data for patients in wave one to those in waves two and three.ResultsWe identified 136 patients with MIS-C. The median age decreased but not significantly during the waves, from 9.9 years to 7.3 years (p = 0.105). Boys represented 52.2% (n = 71) of patients, and 46% (n = 41) of patients originated from sub-Saharan Africa (p < 0.001). Patients presented less diarrhea (p = 0.004), respiratory distress (p < 0.001), and myocarditis (p < 0.001) with progressive waves. Biological inflammation also decreased, namely, C-reactive protein level (p < 0.001), neutrophil count (p = 0.004), and albumin level (p < 0.001). Patients received more corticosteroids (p < 0.001) and required less ventilation support (p < 0.01) and less inotrope treatment (p < 0.001) in the later waves. The duration of hospitalization gradually decreased (p < 0.001), as did critical care unit admissions (p = 0.002).ConclusionOver the three COVID-19 waves, with a change in the management of MIS-C, children in the JIR cohort in France showed a less severe disease course, in particular, a greater use of corticosteroids. This observation may reflect the impact of both improved management and different SARS-CoV-2 variant.